Meningococcemia in a vaccinated child receiving eculizumab and review of the literature - Üçkardeş, Diana; Göknar, Nilüfer; Kasap, Nurhan; Keleşoğlu, Emre; Arga, Mustafa; Candan, Cengiz (The Turkish Journal of Pediatrics, 2023)
Background. Atypical hemolytic uremic syndrome (aHUS) is a rare and severe disease characterized by uncontrolled activation and dysregulation of the alternative complement pathway and development of thrombotic microangiopathy. Eculizumab, which is used as a first-line therapy in aHUS, blocks the formation of C5 convertase and inhibits the formation of the terminal membrane attack complex. It is known that treatment with eculizumab increases the risk of meningococcal disease by 1000-2000-fold. Meningococcal vaccines should be administered to all eculizumab recipients. Case. We describe a girl with aHUS who was receiving eculizumab treatment and experienced meningococcemia with non-groupable meningococcal strains which rarely cause disease in healthy people. She recovered with antibiotic treatment and we discontinued eculizumab. Conclusions. In this case report and review, we discussed similar pediatric case reports in terms of meningococcal serotypes, vaccination history, antibiotic prophylaxis and prognosis of patients who experienced meningococcemia under eculizumab treatment. This case report highlights the importance of a high index of suspicion for invasive meningococcal disease.
Keywords: atypical hemolytic uremic syndrome; child; eculizumab; meningococcemia; vaccine